Single-Nucleotide Polymorphisms in Human NPC1 Influence Filovirus Entry Into Cells - Kondoh, Tatsunari (J Infect Dis, 2018)
Niemann-Pick C1 (NPC1), a host receptor involved in the envelope glycoprotein (GP)–mediated entry of filoviruses into cells, is believed to be a major determinant of cell susceptibility to filovirus infection. It is known that proteolytically digested Ebola virus (EBOV) GP interacts with 2 protruding loops in domain C of NPC1. Using previously published structural data and the National Center for Biotechnology Information Single-Nucleotide Polymorphism (SNP) database, we identified 10 naturally occurring missense SNPs in human NPC1. To investigate whether these SNPs affect cell susceptibility to filovirus infection, we generated Vero E6 cell lines stably expressing NPC1 with SNP substitutions and compared their susceptibility to vesicular stomatitis virus pseudotyped with filovirus GPs and infectious EBOV. We found that some of the substitutions resulted in reduced susceptibility to filoviruses, as indicated by the lower titers and smaller plaque/focus sizes of the viruses. Our data suggest that human NPC1 SNPs may likely affect host susceptibility to filoviruses.